Recovery of Damaged Skeletal Muscle in mdx Mice through Low-intensity Endurance Exercise - Frinchi, M.; Macaluso, F.; Licciardi, A.; Perciavalle, V.; Coco, M.; Belluardo, N.; Morici, G.; Mudò, G. (International Journal of Sports Medicine, 2014)
The lack of dystrophin in mdx mice leads to cycles of muscle degeneration and regeneration processes. Various strategies have been proposed in order to reduce the muscle-wasting component of muscular dystrophy, including implementation of an exercise programme. The aim of this study was to examine how low-intensity endurance exercise affects the degeneration-regeneration process in dystrophic muscle of male mdx mice. Mice were subjected to low-intensity endurance exercise by running on a motorized Rota-Rod for 5 days/week for 6 weeks. Histomorphological analysis showed a significant reduction of measured inflammatory-necrotic areas in both gastrocnemius and quadriceps muscle of exercised mdx mice as compared to matched sedentary mdx mice. The degenerative-regenerative process was also evaluated by examining the protein levels of connexin 39 (Cx39), a specific gene expressed in injured muscles. Cx39 was not detected in sedentary wild type mice, whereas it was found markedly increased in sedentary mdx mice, revealing active muscle degeneration-regeneration process. These Cx39 protein levels were significantly reduced in muscles of mdx mice exercised for 30 and 40 days, revealing together with histomorphological analysis a strong reduction of degeneration process in mice subjected to low-intensity endurance exercise. Muscles of exercised mdx mice did not show significant changes in force and fatigue resistance as compared to sedentary mdx mice. Overall in this study we found that specific low-intensity endurance exercise induces a beneficial effect probably by reducing the degeneration of dystrophic muscle.
Keywords: dystrophic muscle; muscle regeneration; muscle injury; connexin; connexin 39; muscle strength